We can distribute the

2
1

to rewrite the right side of the equation without parentheses. You can think of this as (
2
1

·16x)+(
2
1

·24). Rewrite the right side.
4(2x+4)
=
2
1

(16x+24)

8x+16
=
2
1

(16x+24)

8x + 16
=
+

1 answer

To rewrite the equation without parentheses by distributing the \( \frac{1}{2} \), we can start with the right side:

\[ \frac{1}{2}(16x + 24) \]

Distributing \( \frac{1}{2} \) gives us:

\[ \frac{1}{2} \cdot 16x + \frac{1}{2} \cdot 24 = 8x + 12 \]

Now let's rewrite the equation with the distributed form:

\[ 8x + 16 = 8x + 12 \]

So, the equation simplifies to:

\[ 8x + 16 = 8x + 12 \]

Would you like to solve for \( x \) or do you need further assistance with this equation?